Remembering revolution gender, violence, and subjectivity in India's Naxalbari movement - Roy, Srila (New Delhi : Oxford University Press, 2013)
This text explores the production of cultural memory in relation to women's involvement in the late 1960s' radical Naxalbari movement of West Bengal. Drawing from historiographic, popular and personal memoirs, it provides an innovative conceptual analysis of the Naxalbari movement principally in terms of gender, violence, and subjectivity.
Description based on online resource; title from home page (viewed on Dec. 20, 2012).
Includes bibliographical references and index.
Keywords: Naxalite movement; Sex discrimination -- India